Community Empowerment Based on Islamic Philanthropy through the BAZNAS Ciamis Zakat Village Program - Nida Nadia Zakiyyatunnisa; Abdul Basit (LP2M of Institute for Research and Community Services - UIN Walisongo, 2026)
This community service activity was motivated by the importance of Islamic philanthropy-based community empowerment as a form of da'wah bil-hal that promotes social transformation and community independence. The BAZNAS Zakat Village Program in Ciamis Regency integrates social, economic, educational, health, and religious empowerment. The method used was Participatory Action Research (PAR) through observation, participatory mentoring, interviews, documentation, and reflective evaluation involving program managers and beneficiaries. The results show that the program positively improved community welfare by strengthening economic capacity, increasing educational access, providing social protection for vulnerable groups, and reinforcing spiritual values. Based on Jim Ife’s theory, the program reflects three empowerment dimensions: enabling, empowering, and protecting. It also represents da'wah bil-hal through the values of real charity, exemplary conduct, social concern, and public welfare. Therefore, the Zakat Village Program is an effective and sustainable Islamic philanthropy-based empowerment model.